براہوئی متل و وساہت آ سماجی او نفسیاتی پس منظر: Social and Psychological Background of Brahui Proverbs and Quotations - Shahwani, Hameed (Al-Burz, 2010)
This research paper describes social psychology of nomadic life it shows the differentiation between inexperienced and a qualified individual although the Brahui proverbs idioms riddle and quotations are recited by unqualified persons but they have a particular lesson in it finally this paper describes the life history of Baloch inhabitant’s ups and downs of their existence۔